Pengaruh Kualitas Produk, Kepercayaan dan Citra Merek terhadap Kepuasan Pelanggan Wardah di Kota Batam - Tio, Michelle; Evyanto, Winda (Jurnal Disrupsi Bisnis, 2024)
This research aims to examine the influence of product quality, trust and brand image on Wardah customer satisfaction in Batam City. The population used is users who have used Wardah products, but the number is uncertain. So this type of research is quantitative research with a sampling technique using the Lemeshow formula with a total calculation of 100 respondents. Data collection was carried out through distributing questionnaires and data analysis using data quality tests, such as validity tests, reliability tests, and classical assumption tests including normality tests, multicollinearity tests, and heteroscedasticity tests. The influence test uses multiple linear regression analysis and determinant coefficient analysis, while the hypothesis test uses the t test and f test. The results of multiple linear regression analysis show that product quality, trust and brand image significantly influence customer satisfaction, with the product quality variable having an influence of 18.1% on customer satisfaction. Trust has an influence of 35.5% on customer satisfaction. Brand image has an influence of 58.2% on customer satisfaction. Findings in testing the coefficient of determination (R2) show that product quality, trust and brand image together account for 67.2% of the variation in customer satisfaction. Apart from that, testing using the t test and F test shows that product quality, trust and brand image individually and as a whole have a positive and significant influence on Wardah customer satisfaction in Batam City.